Backcasting supports cross-sectoral collaboration and social-technical innovation bundling: case studies in agri-food systems - Remans, Roseline; Zornetzer, Heather; Mason-D’Croz, Daniel; Kugler, Cody; Thornton, Philip; Pedersen, Charlotte; Cattaneo, Francoise; Samantaray, Debjani; Brouwer, Inge D.; Bosch, Diane; Bekele, Tesfaye Hailu; Martinez, Silvia; et al. (Frontiers in Sustainable Food Systems, 2024)
There is a clear and urgent call to transform our food systems as a critical nexus to tackle ongoing global climate, biodiversity, equity, and nutrition crises. Many food and agricultural innovations are being developed and scaled but these innovations often target sector-specific problems and remain disconnected from the more complex demand for transformative change at scale. To bridge this demand for systemic change within the innovation ecosystem, initiatives are applying various approaches such as visioning, holistic assessments, innovation portfolio management and multistakeholder co-creation. Here we report on insights from applying a food systems tailored backcasting approach in a diversity of settings since 2021, including a national food system dialogue, a youth business innovation challenge, a landscape multi-stakeholder platform, a public-private sector co-learning session, an agroecological transitions program, and a hybrid food systems university course for graduate students and global professionals. We thereby build on existing literature and case studies of how change happens (or does not happen) and aim to use those insights to support food systems change makers. Across these settings, the backcasting approach asks participants to connect innovations with broader systems-change visions, to anticipate tradeoffs for multiple food system outcomes and population groups, and to cross sectoral boundaries. The use cases demonstrate that the backcasting process contributes to changes in views, practices and structures that participants work with. Specifically, it supports moving beyond “silver bullet” innovation approaches, the bundling of social and technical innovations, and building action-oriented cross-sectoral bridges. Food systems change is complex and innovations alone are insufficient to address its complexity. But innovations can play a positive role if connected to more holistic systems-change processes and goals. Considering strengths and limitations of the backcasting approach, the diversity of practical applications supports its potential to connect innovations to holistic food systems visions, to strengthen cross-sectoral collaboration and to bundle social and technical innovations for desirable food systems change.